2016
DOI: 10.1111/jcmm.13024
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes: a potential defender in the spleen of Npc1 mutant mice

Abstract: Niemann–Pick disease, type C1 (Npc1), is an atypical lysosomal storage disorder caused by autosomal recessive inheritance of mutations in Npc1 gene. In the Npc1 mutant mice (Npc1−/−), the initial manifestation is enlarged spleen, concomitant with free cholesterol accumulation. Telocytes (TCs), a novel type of interstitial cell, exist in a variety of tissues including spleen, presumably thought to be involved in many biological processes such as nursing stem cells and recruiting inflammatory cells. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Our results demonstrate the rise in spleen weight of untreated Npc1 −/− and treated Npc1 −/− and Npc1 +/+ mice. In previous studies, an increase of spleen weight of untreated Npc1 −/− had already been shown due to extensively infiltrated foam cells [50], which is in agreement with our results. However, while weight increased during combination therapy, in particular by HPßCD [51], we report here an increase in the spleen/body weight ratio.…”
Section: Discussionsupporting
confidence: 94%
“…Our results demonstrate the rise in spleen weight of untreated Npc1 −/− and treated Npc1 −/− and Npc1 +/+ mice. In previous studies, an increase of spleen weight of untreated Npc1 −/− had already been shown due to extensively infiltrated foam cells [50], which is in agreement with our results. However, while weight increased during combination therapy, in particular by HPßCD [51], we report here an increase in the spleen/body weight ratio.…”
Section: Discussionsupporting
confidence: 94%
“…TCs are identified in a wide variety of organs from diverse species including mammals 8 11 , avian 12 , 13 , reptiles 14 , Amphibians 15 and aquatic species 16 , 17 and parasitic worm 18 . They are located in the trachea and lungs 19 , heart 20 and the blood vessels 21 , kidney, ureter, urinary bladder 22 , tongue 23 , oesophagus, stomach and small and large intestines 24 , liver , pancreas 14 , testis 25 , prostate 26 , efferent ductules 27 ovaries, oviducts, uterus, vagina, mammary glands and placenta 26 , spleen 8 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, TCs entered this scenario as a new distinctive type of interstitial cells that may potentially behave as nursing cells for SC-mediated skeletal muscle regeneration. However, it must be frankly recognized that such supporting role for TCs has only been supposed on the basis of their in situ identification in the close vicinity of SCs in healthy skeletal muscles 10,1315,17 , their possible role during early myogenesis 28 , and their well-documented interaction and/or cross-talk with stem/progenitor cells in other organs 3,10,2934 . Indeed, at present, the effective occurrence of a morpho-functional interplay between TCs and SCs in injured skeletal muscles has yet to be demonstrated with certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, afterwards the number of TCs appears to be robustly reduced in fetal skeletal muscle tissues at 12 weeks of gestation, where mature myotubes become evident, suggesting that TCs may specifically be implicated in myotube development/formation during the early maturation steps of muscle tissue morphogenesis 28 . Besides the aforementioned experimental data, the intriguing hypothesis of a morpho-functional interaction between TCs and SCs during muscle repair/regeneration is also based on the increasing evidence that TCs may establish a specialized relationship with putative stem/progenitor cells endowed with regenerative potential in a variety of healthy, injured or pathological tissues/organs 3,10,2934 . In this context, TCs may help in recruiting, nursing or guiding such progenitors to proliferate, differentiate and integrate into the tissue architecture.…”
Section: Introductionmentioning
confidence: 99%